Management of Distribution Programs "Non Cash Food Aid" in Rembang District - Melly Anggraeni; Hardi Warsono; Ida Hayu Dwimawanti (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
In the context of poverty reduction, the Government mandates the distribution of Non-Cash Food Assistance. Non-Cash Food Aid, hereinafter abbreviated as BPNT, is a policy of the Central Government in the form of food social assistance in the form of non-cash given to Beneficiary Families (KPM) every month through electronic accounts and is only used to buy food in E-warong in collaboration with banks. In BPNT distribution management in Rembang Regency, the planning aspect begins with the data collection and validation of population data, with the aim of channeling BPNT on target. Organizing is done in coordination between the Ministry of Social Affairs, Social Services, Women's Empowerment and Family Planning District. Rembang, BNI, and e-warong agents in each district. The implementation was carried out in stages, by distributing non-cash assistance of Rp 110,000.00 per family. Supervision is carried out in coordination with BNI, because the distribution system uses electronic money. The obstacle faced is that there are still residents who are eligible for assistance, but have not been distributed by BPNT. So in the future there needs to be up to date data validation. In the future, the distribution will be more on target.